2018
DOI: 10.11628/ksppe.2018.21.3.243
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Forest Education Program in Urban Natural Park on Elementary School Students’ Academic Stress and Ego-Resilience

Abstract: The purpose of this study was to investigate the effect of forest education program on elementary school students' academic stress and ego-resilience. The subjects of this study were 20 elementary school boys and girls who applied for a youth group forest experience program in OO-dong, Incheon. The duration of the experiment was 12 weeks from September 2 to November 18, 2017 and each session was held once a week and the run time of a session was 90 minutes. Before and after the implementation of the forest edu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
1
0
0
Order By: Relevance
“…Furthermore, it is in line with previous research proving the job-seeking stress reduction effect in the pretest and posttest after carrying out 8 sessions of the forest therapy program for approximately 2 months with 70 subjects (Lee, 2015). It is also consistent with previous research proving the academic stress reduction effect in the pretest and posttest after carrying out 12 sessions of the forest therapy program for approximately 2 months with 20 elementary school students (Jeong, 2018). Accordingly, this study examined and confirmed the persistence of the forest therapy program that has not been covered in previous studies.…”
Section: Test For Homogeneity Of Academic and Job-seeking Stress Betwsupporting
confidence: 91%
“…Furthermore, it is in line with previous research proving the job-seeking stress reduction effect in the pretest and posttest after carrying out 8 sessions of the forest therapy program for approximately 2 months with 70 subjects (Lee, 2015). It is also consistent with previous research proving the academic stress reduction effect in the pretest and posttest after carrying out 12 sessions of the forest therapy program for approximately 2 months with 20 elementary school students (Jeong, 2018). Accordingly, this study examined and confirmed the persistence of the forest therapy program that has not been covered in previous studies.…”
Section: Test For Homogeneity Of Academic and Job-seeking Stress Betwsupporting
confidence: 91%